2019
DOI: 10.1002/cpt.1354
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Regulatory Science Is Meeting Evolution of Clinical Evidence Generation

Abstract: At the turn of the century, the pharmaceutical industry began a transition toward a focus on oncology, rare diseases, and other areas of high unmet need that required a new, more complex approach to drug development. For many of these disease states and novel approaches to therapy, traditional approaches to clinical trial design fall short, and a number of innovative trial designs have emerged. In light of these changes, regulators across the globe are implementing new programs to provide regular development p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Fox Foundation convened a group of leading experts with the objective of improving the development of therapeutics for PD through the use of reliable digital endpoints. One gap that has been highlighted in the area of DHT is the lack of open-access consensus data standards that have been accepted by the community [34]. A diverse working group of data scientists, pharmaceutical companies, and data standard consortium partners codeveloped a comprehensive roadmap for metadata standards for DHT.…”
Section: Michael J Fox Foundation Digital Health Consortiummentioning
confidence: 99%
“…Fox Foundation convened a group of leading experts with the objective of improving the development of therapeutics for PD through the use of reliable digital endpoints. One gap that has been highlighted in the area of DHT is the lack of open-access consensus data standards that have been accepted by the community [34]. A diverse working group of data scientists, pharmaceutical companies, and data standard consortium partners codeveloped a comprehensive roadmap for metadata standards for DHT.…”
Section: Michael J Fox Foundation Digital Health Consortiummentioning
confidence: 99%
“…This is particularly key with recent COVID-19-stimulated changes in the regulatory landscape, which supports the need for more flexible approaches. An example is a relatively recent shift of the proportion of the overall pharmaceutical development portfolio from small molecules or antibody-based programs to newer therapeutic modalities, which do not lend themselves well to the timing and comprehensive data requirements of traditional decision-making milestones inherent in development plans anchored in progression from phase I, II, and III [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Ohno[20]and Dennis[ 24 ], pulmonary artery perfusion in malignant lesions was higher than in benign lesions, which was consistent with our findings. Some studies [ 25 27 ]have found that pulmonary malignant lesions were mainly bronchial blood supply, benign lesions were mainly pulmonary artery blood supply. This was contrary to our results, maybe our study selected lung lesions larger than 2 cm in diameter, leading to an increase in pulmonary artery blood supply.…”
Section: Discussionmentioning
confidence: 99%